Shear lag analysis by the adaptive finite element method - Lee, Chi King (2014)
Due to the presence of sharp stress gradients, traditional finite element analysis using uniform meshes for the solution of shear lag problems for thin-walled structures is inefficient and will result in inaccurate values of effective breadth ratio. By using the adaptive finite element analysis, it is possible to obtain results with predetermined accuracy with a minimum amount of computational cost. An adaptive finite element analysis procedure is used to deal with the problem of shear lag effects of plated structures with arbitrary dimension and geometry. This study consists of two parts. In Part 1 of the study, shear lag effects in simple plated structures, such as straight rectangular, single-cell box girders are studied. In Part 2 of the study, the adaptive refinement procedure will be extended to the shear lag analysis of complex plated structures such as core walls with openings, multi-cell box girders and box girders with curve flanges.